Variation in sediment and seagrass characteristics reflect multiple stressors along a nitrogen‐enrichment gradient in a New England lagoon. Issue 3 (28th January 2022) - Haviland, Katherine Ann; Howarth, Robert Warren; Marino, Roxanne; Hayn, Melanie
Abstract: We examined concentrations of organic carbon, dissolved sulfides, total sediment sulfur, and stable sulfur isotope ratios in seagrass leaf tissues across a nitrogen‐enrichment gradient in a coastal marine ecosystem (Cape Cod, Massachusetts) in 2007–2010 and 2017–2019. We also measured seagrass aboveground and belowground biomass, epibiota biomass, and leaf chlorophyll content. Seagrasses were present at all sites in the former period but were lost at our most nitrogen‐impacted site (Snug Harbor) by 2011. In 2007–2010, sediment organic carbon and dissolved sulfides were highest in Snug Harbor and decreased along the gradient; leaf tissues depleted in 34 S also indicated higher sulfide intrusion into seagrass tissues in more eutrophic areas. By 2017–2019, sediment organic carbon and pore‐water soluble sulfides had decreased in Snug Harbor, but had increased at the intermediate site, to levels found at the most impacted site prior to the seagrass die‐off. Again, leaf tissue 34 S depletion reflected this pattern, indicating seagrasses were exposed to the highest sulfides at the intermediate site. The decreases in sediment organic carbon and soluble sulfides in Snug Harbor years after the loss of the seagrasses illustrate a feedback between high organic matter in seagrass beds and increasing stressors like elevated soluble sulfides in nutrient‐enriched systems. We found significant relationships between sediment conditions and seagrass responses, including greater aboveground to belowground biomass ratios, epibiota biomass, and 34 S‐depleted leaves at sites with high pore‐water sulfide and highly organic sediments. Our research suggests that the reduction of anthropogenic nitrogen entering the harbor is necessary for improving sediment quality and preventing seagrass mortality.